EFEKTIVITAS GAYA KEPEMIMPINAN KEPALA SEKOLAH TERHADAP KINERJA GURU - Epi Supriyani Siregar; Fatin Nadifa Tarigan (Institut Pendidikan Tapanuli Selatan, 2023)
This study aims to find out the effectiveness or influence of the Principal's Leadership Style on Teacher Performance at SMKN 1 Percut Sei Tuan. This study used quantitative methods. Data collection techniques used were observation, questionnaires, interviews and documentation techniques. The data analysis technique used were descriptive statistical analysis and inferential statistical analysis. The results of this study indicate that the principal's leadership has a positive influence on teacher performance. Thus it can be stated that the principal's leadership style was very good. It is due to the school schedule and good direction, the principal was motivated to teach, and the principal paid attention to the availability of learning facilities including technology facilities in schools.